2020
DOI: 10.1016/s0140-6736(20)32113-9
|View full text |Cite
|
Sign up to set email alerts
|

The opioid crisis and the 2020 US election: crossroads for a national epidemic

Abstract: and education sectors are reopening, and countries are benefiting from the experiences of others as they continue to live with the COVID-19 pandemic and develop more effective control strategies.We are all members of the WHO Strategic and Technical Advisory Group for Infectious Hazards and declare no competing interests.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 7 publications
0
17
0
1
Order By: Relevance
“…With respect to psychosocial interventions, a Cochrane review found that patients receiving psychosocial interventions in addition to OAT did not show improved outcomes compared to individuals receiving OAT alone; whereas another systematic review did support their efficacy to improve clinical outcomes [34]. There is emerging evidence that some of these inconsistent findings may be indicative of other variables impacting patient responses to psychiatric treatment, including ongoing substance use and complex psychosocial such as housing and employment [9,33,35].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With respect to psychosocial interventions, a Cochrane review found that patients receiving psychosocial interventions in addition to OAT did not show improved outcomes compared to individuals receiving OAT alone; whereas another systematic review did support their efficacy to improve clinical outcomes [34]. There is emerging evidence that some of these inconsistent findings may be indicative of other variables impacting patient responses to psychiatric treatment, including ongoing substance use and complex psychosocial such as housing and employment [9,33,35].…”
Section: Discussionmentioning
confidence: 99%
“…In Canada, overdose deaths and hospitalizations related to opioid use disorder (OUD) have remained high despite increasing awareness and intervention [5,6]. In the United States, opioids are involved in the majority of deaths related to drug overdose, which rose to an all-time high in 2019 with 49,860 overdose deaths involving opioids [7][8][9]. The impacts of the COVID-19 pandemic have additionally exacerbated preexisting issues relating to access to appropriate treatment and interventions, ensuring that the opioid crisis will remain an ongoing concern for patients and families, healthcare workers, and policymakers alike [9].…”
Section: Introductionmentioning
confidence: 99%
“…4,5 Since 2019, opioid overdoses have increased 30%. 6 While overdose is a common cause of death in those with opioid dependence, opioid dependence is also associated with increased risk of suicide, cancer, and cardiovascular disease. 5,7,8 Opioid agonist treatment, also known as medication-assisted therapy, is a promising management strategy for those with opioid dependence, with the World Health Organization recommending methadone and buprenorphine as essential medications for opioid agonist treatment as these medications may reduce the risk of overdose and thus mortality.…”
Section: Commentarymentioning
confidence: 99%
“…Since the onset of the opioid epidemic two decades ago, half a million Americans have perished from opioid overdose ( Wen & Sadeghi, 2020 ; Wilson et al, 2020 ). In the first 12 months of the COVID-19 pandemic (March 2020 through February 2021), the Centers for Disease Control and Prevention ( CDC, COVID Data Tracker, 2021 ) reported a similar number succumbed to the coronavirus in a fraction of the time.…”
Section: Introductionmentioning
confidence: 99%